DPPH radical scavenging activity of xylo-oligosaccharides mixtures of controlled composition: A step forward in understanding structure–activity relationship. (February 2023) - Fuso, Andrea; Dejonghe, Winnie; Cauwenberghs, Lieve; Rosso, Ginevra; Rosso, Franco; Manera, Ileana; Caligiani, Augusta
Graphical abstract: Highlights: XOS mixtures with different structures were produced starting from standard xylan. A mixture of XOS with DP 6–9 was obtained through preparative SEC purification. Further knowledge has been gained about in vitro antioxidant activity of XOS. Abstract: Antioxidant activity of oligosaccharides is very discussed, and the relationship between their chemical structure and functionality is not clear. In this work, XOS, with different degrees of polymerization, acetylation and purity were produced starting from commercial xylans by enzymatic hydrolysis coupled with tangential ultrafiltration. A purified mixture containing DP 6–9 XOS was also produced. A detailed molecular characterization of all the XOS mixtures was performed by LC-MS, HPSEC-RID and 1 H NMR. In vitro antioxidant activity was then tested against the stable DPPH free-radical. It was found that standard pure xylose and DP 2–6 XOS had very low scavenging capacity, while DP 6–9 XOS had a great one. In general, unsubstituted XOS are more antioxidant than acetylated ones, and a higher DP favours an increase in this functionality at first, then a decrease when molecular weights become higher.